Feasibility of Presurgical Exercise in Men With Prostate Cancer Undergoing Prostatectomy - Favil Singh PhD; Robert U. Newton PhD; Michael K. Baker PhD; Nigel A. Spry MBBS, PhD; Dennis R. Taaffe PhD; Jeffery Thavaseelan MBBS; Daniel A. Galvão PhD (Integrative Cancer Therapies, 2017)
Background: Prostatectomy is associated with short- and long-term morbidity, which includes attenuation of muscle function and deterioration of lean body mass. Physical function is a known predictor of morbidity and mortality, with initial evidence indicating that presurgical exercise is associated with fewer postsurgical complications and shorter hospitalization. The aim was to determine the feasibility of a supervised presurgical exercise program for prostate cancer (PCa) patients scheduled for prostatectomy. Methods: Ten men (68+6.4 years old) with localized PCa undertook a 6-week resistance and aerobic exercise program prior surgery. Training was undertaken twice weekly and patients were assessed at baseline, presurgery, and 6 weeks postsurgery. Outcome measures included muscle and physical performance, body composition, urinary incontinence and questionnaire. Results: Muscle strength increased by 7.5% to 24.3% ( P < .05) from baseline to presurgery but decreased to pretraining levels postsurgery, except for knee extensor strength ( P = .247). There were significant improvements ( P < .05) in the 6-m fast walk (9.3%), 400-m walk (7.4%), and chair rise (12.3%) at presurgery. Following surgery, improvements in physical performance were maintained. There was no change in lean or fat mass prior to surgery, but lean mass declined by 2.7 kg ( P = .014) following surgery. There were no adverse effects from the exercise program. Conclusions: Exercise undertaken prior to prostatectomy improved muscle and physical performance, with functional benefits maintained 6 weeks postsurgery. Presurgical exercise for PCa patients has the potential to facilitate recovery by improving physical reserve capacity, especially in men with poor muscle nd physical performance.